Respostas
respondido por:
0
Ola Beca
f(x) = 3ˣ
g(x) = (1/4)ˣ
f(0) = 3^0 = 1
f(1) = 3^1 = 3
f(-4) = 3^-4 = 1/81
f(1/3) = 3^(1/3) = 1/27
g(1) = (1/4)^1 = 1/4
g(2) = (1/4)^2 = 1/16
g(-3) = (1/4)^-3 = 4^3 = 64
g(1/2) = (1/4)^1/2 = 1/2
.
f(x) = 3ˣ
g(x) = (1/4)ˣ
f(0) = 3^0 = 1
f(1) = 3^1 = 3
f(-4) = 3^-4 = 1/81
f(1/3) = 3^(1/3) = 1/27
g(1) = (1/4)^1 = 1/4
g(2) = (1/4)^2 = 1/16
g(-3) = (1/4)^-3 = 4^3 = 64
g(1/2) = (1/4)^1/2 = 1/2
.
Beca1620:
esse é da letra (a ??
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás